A Comparative Study between PI, PD and PID Controllers to Control Motor Speed - Ali, Fadya Faiz; Matoog, Fatma Milad (جامعة بنغازي - كلية الآداب والعلوم بالمرج, 2022)
تستخدم محركات DC على نطاق واسع في الصناعات لأغراض مختلفة. تتطلب العديد من المواقف تغييرات في سرعة محرك التيار المستمر، وهذا يستلزم تطوير طريقة للتحكم الفعال في سرعة محرك التيار المستمر. هناك أنواع تحكم تقليدية ورقمية، متناسب متكامل (PI) مشتق متناسب (PD) ومشتق تكاملي متناسب (PID) يستخدم للتحكم في سرعة محرك التيار المستمر. في هذا المشروع، يتم نمذجة ومحاكاة PI وPD وPID في MATLAB SIMULINK للتحكم في سرعة محرك التيار المستمر. قامت وحدات التحكم المذكورة أعلاه بتحليل وتقييم أربعة شروط تجاوز السرعة ووقت الصعود وخطأ الحالة المستقرة ووقت التسوية، والغرض من التقييم للعثور على أفضل أداء للتحكم في سرعة محرك التيار المستمر نتيجة لذلك، تعد PID أفضل وحدة تحكم نظرا لتحسين الأداء عند مقارنتها بوحدات التحكم الأخرى. DC Motors are widely used in industries for various purposes. Many situations demand changes in the speed of the DC Motor, and this makes necessity to develop a method to effectively control the speed of DC motor. There are conventional and digital controller types, Proportional Integral (PI), Proportional Derivative (PD), and Proportional Integral Derivative (PID) used to control speed of the DC motor. In this project PI, PD and PID is modeling and simulated in MATLAB SIMULINK to control speed of the DC Motor. Aforementioned Controllers analyzed and evaluated on four terms overshoot, rise time, steady state error and settling time, the purpose of the evaluation to find the best performance to control the speed of DC motor. As a result of this, PID is the best controller due to it is improved performance when compared with others controllers.
Keywords: محركات التيار -- وحدات التحكم -- التحكم الصناعي -- التغذية المرتدة